The impact of prenatal inflammatory priming on the neuron-microglia proteines expression in young offspring brain: immunohistochemical study in neurodevelopmental model of schizophrenia - Basta-Kaim, Agnieszka; Chamera, Katarzyna; Trojan, Ewa; Bryniarska, Natalia; Szuster, Magdalena; Budziszewska, Bogusława (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: A number of studies suggest that in brain microglia are held in a surveillant and quiescent state of activation through several inhibitory signaling dyads. Recently the fractalkine (CX3CL1) and its receptor (CX3CR1) as well as CD200 and CD200 receptor (CD200R) are particularly noteworthy, because disruption of these networks extended the duration of pro-inflammatory response, mainly via malfunction of a unique communication system between neuron-microglia cells. Objective: To explore the possibility that maternal inflammatory priming based on the bacterial endotoxin (lipopolisaccharide, LPS) administration might serve as a trigger to disturbances in CX3CL1-CX3CR1 and CD200-CD200R signaling in the brain of young offspring. Material and Methods: Pregnant females were injected subcutaneously with LPS at a dose of 2 mg/kg every second day from the seventh day of pregnancy until the delivery. Control pregnant rats were left undisturbed in their homecages. At 7 days of age, control and prenatally LPS-treated rats were decapitaded and hippocampi and frontal cortices were dissected. Immunohistofluorescent staining was performed using primary antibodies: anti-CX3CL1, anti-OX2 and anti-CX3CR1 as well as anti-OX2R. Moreover proteins were co-stained with neuronal (anti-MAP2), astroglial (anti-GFAP) and microglial markers (anti-Iba1), to clearly demonstrate the co-localization of CX3CL1, CD200, CD200R and CX3CR1 with brain cells in selected areas of hippocampus and frontal cortex of young offspring. Results: First we demonstrated the localization of CX3CL1 and CD200 mainly on neuronal cells, while CX3CR1 and CD200R on microglial cells in hippocampus and frontal cortex of young offspring. Analyzing both ligands localization we observed that maternal LPS administration tender to increase the expression of neuronal CX3CL1 in hippocampus, while CD200 in both examined brain areas. On the other hand, maternal immune challenge in the opposite way affects the microglial expression of CX3CR1 and CD200R. Prenatal exposure to LPS have been found to increase the CX3CR1 expression in hippocampus regions, while decrease a staining of CD200R in hippocampus and also in the frontal cortex of young offspring. Conclusions: These immunohistofluorescent data provide evidence that maternal exposure to immune challenges induce malfunction of neuron-microglia proteines staining in brain areas of young offspring. Thus phenomenon, termed prenatal neuroinflammatory priming, via disruption of homeostatic mechanisms regulating brain immune system, may be a key factor leading to the occurrence of schizophrenia-like behavioral deficits observed in adult animals in commonly accepted neurodevelopmental model of this disease.